Site-Specific Bioconjugation of an Organometallic Electron Mediator to an Enzyme with Retained Photocatalytic Cofactor Regenerating Capacity and Enzymatic Activity - Sung In Lim; Sungho Yoon; Yong Hwan Kim; Inchan Kwon (Molecules, 2015)
Photosynthesis consists of a series of reactions catalyzed by redox enzymes to synthesize carbohydrates using solar energy. In order to take the advantage of solar energy, many researchers have investigated artificial photosynthesis systems mimicking the natural photosynthetic enzymatic redox reactions. These redox reactions usually require cofactors, which due to their high cost become a key issue when constructing an artificial photosynthesis system. Combining a photosensitizer and an Rh-based electron mediator (RhM) has been shown to photocatalytically regenerate cofactors. However, maintaining the high concentration of cofactors available for efficient enzymatic reactions requires a high concentration of the expensive RhM; making this process cost prohibitive. We hypothesized that conjugation of an electron mediator to a redox enzyme will reduce the amount of electron mediators necessary for efficient enzymatic reactions. This is due to photocatalytically regenerated NAD(P)H being readily available to a redox enzyme, when the local NAD(P)H concentration near the enzyme becomes higher. However, conventional random conjugation of RhM to a redox enzyme will likely lead to a substantial loss of cofactor regenerating capacity and enzymatic activity. In order to avoid this issue, we investigated whether bioconjugation of RhM to a permissive site of a redox enzyme retains cofactor regenerating capacity and enzymatic activity. As a model system, a RhM was conjugated to a redox enzyme, formate dehydrogenase obtained from Thiobacillus sp. KNK65MA (TsFDH). A RhM-containing azide group was site-specifically conjugated to p-azidophenylalanine introduced to a permissive site of TsFDH via a bioorthogonal strain-promoted azide-alkyne cycloaddition and an appropriate linker. The TsFDH-RhM conjugate exhibited retained cofactor regenerating capacity and enzymatic activity.